Natural killer cell activities of synbiotic Lactobacillus casei ssp. casei in conjunction with dextran - Ogawa, T (Blackwell Science Inc, 2006)
We have reported previously that Lactobacillus casei ssp. casei, together with specific substrate dextran, exhibited an adjuvant effect of stimulating humoral immune responses against bovine serum albumin (BSA) as a model antigen in BALB/c mice. In the present study, among the Lactobacillus species tested, L. casei ssp. casei with dextran significantly elevated the natural killer (NK) cell activites in spleen mononuclear cells from BALB/c mice in comparison to L. casei ssp. casei alone or other Lactobacillus species with or without dextran. Oral administration of L. casei ssp. casei together with dextran also resulted in a significant increase of NK cell activities in healthy human volunteers. Further, L. casei ssp. casei induced significant production of interleukin (IL)-12 in human peripheral blood mononuclear cells and IL-15 mRNA expression in the human intestinal epithelial cell line Caco-2. L. casei ssp. casei with dextran in food also significantly elevated the survival rate of BALB/c mice bearing Meth-A cells. Taken together, these results demonstrate that dietary synbiotic supplementation which is a combination of the L. casei ssp. casei used as a probiotic together with the dextran, a specific substrate as a prebiotic, efficiently elicits murine and human NK cell activities.